UNIVERSAL AND CULTURE-SPECIFIC VALUE CONCEPTS IN THE AXIOLOGICAL VOCABULARY OF ENGLISH AND UZBEK - Islomova Zahro Shuhrat qizi; Prof. N. Yuldosheva (Bright Mind Publishing, 2025)
This article investigates universal and culture-specific value concepts in the axiological vocabulary of English and Uzbek. Using a comparative-typological and cognitive-cultural approach, it analyses a corpus of literary works, folklore and media texts to identify moral, ethical and aesthetic values expressed in both languages. The study reveals common human ideals as well as culturally distinctive categories, demonstrating how linguistic choices embody national worldviews and contribute to a deeper understanding of intercultural communication and evaluative semantics.
Keywords: Axiological vocabulary; value concepts; comparative-typological analysis; cognitive-cultural approach; intercultural communication; evaluative semantics; English; Uzbek.